Teacher educators' perspectives on preparing student teachers to work with pupils who speak languages beyond English. Issue 2 (15th March 2021) - Flockton, Gabrielle; Cunningham, Clare
ABSTRACT: Despite a well-documented and significant increase in the population of children in UK schools who speak language(s) beyond English at home, the national Newly Qualified Teacher survey regularly reports that new teachers do not feel confident or prepared to work effectively with 'EAL children'. Whilst understanding the experiences and exploring the attitudes of newly-qualified, in-service and experienced teachers have been the subject of research around the world, the perspectives of teacher educators have not been adequately researched. This article reports on a mixed-methods study investigating teacher educators' views on their role in preparing future teachers to work effectively with multilingual children. A survey was conducted with 62 teacher educators who have responsibility for inclusion or EAL teacher training, which was followed up with a series of semi-structured interviews. Key findings suggest that there may be a mismatch between the perceptions of teacher educators and newly qualified teachers, as the vast majority of the participants reported that they were either confident or very confident about teaching student teachers how to teach EAL children. Additional themes explored were related to concerns over a performativity culture in education, and to balancing linguistic diversity training alongside other pressing priorities in initial teacher education.